2016
DOI: 10.1016/j.blre.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The prothrombotic activity of cancer cells in the circulation

Abstract: The hemostatic system is often subverted in patients with cancer, resulting in life-threatening venous thrombotic events. Despite the multifactorial and complex etiology of cancer-associated thrombosis, changes in the expression and activity of cancer-derived tissue factor (TF) – the principle initiator of the coagulation cascade – are considered key to malignant hypercoagulopathy and to the pathophysiology of thrombosis. However, many of the molecular and cellular mechanisms coupling the hemostatic degenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 114 publications
(164 reference statements)
1
76
0
3
Order By: Relevance
“…Similarly, activated platelets express phosphatidylserine, which catalyzes the production of thrombin and in turn converts fibrinogen into fibrin. Fibrin formation has been implicated in strengthening heterotypic platelet-cancer aggregates, ensuring their survival and transport to secondary sites [26]. …”
Section: Platelet-derived Soluble Factors and Receptors Promote Metasmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, activated platelets express phosphatidylserine, which catalyzes the production of thrombin and in turn converts fibrinogen into fibrin. Fibrin formation has been implicated in strengthening heterotypic platelet-cancer aggregates, ensuring their survival and transport to secondary sites [26]. …”
Section: Platelet-derived Soluble Factors and Receptors Promote Metasmentioning
confidence: 99%
“…This process has been proposed to act as a positive feedback activation loop during cancer metastasis. Moreover, tumor cell-induced platelet activation may play a role in the development of cancer-associated thrombosis [26, 28]. …”
Section: Activation Of Platelets By Cancer Cellsmentioning
confidence: 99%
“…The observed CTC clusters numbered from two to several cells in clinical samples [4,7] and even up to 50 cells in animal experiments [15,16]. It has also been observed that CTC emboli can contain other cells, such as platelets, that may guard the tumor cells from immune elimination and promote their arrest at the endothelium [14,42]. …”
Section: The Dynamics Of Circulating Tumor Cell Microembolimentioning
confidence: 99%
“…The pattern of the blood flow and its shear stress, as well as the movement of other cells in the circulation system can affect CTC trajectory. Moreover, CTCs may also be exposed to collisions with red blood cells or adhesion to leukocytes, platelets, and microphages [42,51,66]. How individual CTCs and CTC emboli can withstand these intercellular interactions and persist in the fluid flow is not yet fully understood, and many questions are still unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…It is now well established that thrombocytosis and elevated circulating tissue factor levels are predictors of latter stage cancer along with increased incidence (4–8 fold) of venous thrombosis. A body of work demonstrates that platelets have the capability of interacting with circulating tumor cells (CTC) either directly or as a fibrin-associated network with neutrophils, and in so doing, prolonging the CTC circulatory half-life (7). Additionally, platelets have been reported to trigger Epithelial-Mesenchymal Transition (EMT) of cancer cells (810).…”
Section: Introductionmentioning
confidence: 99%